Encyclopedia of Latin American and Caribbean literature, 1900-2003 - Balderston, Daniel, 1952-; Gonzalez, Mike, 1943- (Routledge, 2004)
" ... draws together entries on all aspects of literature including authors, critics, major works, magazines, genres, schools and movements in these regions from the beginning of the twentieth century to the present day."--Publisher's description